Transformation of The Students Paradigm in Islamic Education Through The Utilization of Artificial Intelligence - Abdul Rahim Karim; Hendi Sugianto; Ely Fitriani (Yayasan Avicenna, 2024)
This research aims to uncover the transformation of the students paradigm in Islamic education through the utilization of Artificial Intelligence. The approach used in this research is a qualitative approach, relying on literature review as an effective research method in achieving the research objectives. Data collection was conducted systematically and structured through literature analysis focused on the transformation of the students paradigm in Islamic education through the use of Artificial Intelligence. Data analysis was conducted using modified analytical induction techniques to ensure a comprehensive and structured picture, so that the findings are accurate and avoid subjectivity bias. The results of this study describe the transformation of the students paradigm in Islamic education through the use of Artificial Intelligence which can be divided into students models as recipients, collaborators, and leaders. Students as recipients are responsible for responding to predetermined knowledge sequences, following procedures and learning paths, and carrying out learning activities through the use of Artificial Intelligence to achieve predetermined goals. Students as collaborators interact with the Artificial Intelligence system to achieve better and more efficient learning. Meanwhile, students as leaders take the role of controllers to become leaders in their own learning process, manage the risk of Artificial Intelligence decision automation, and develop better and more efficient learning.